Steady and unsteady experimental analysis of a turbocharger for automotive applications. (15th July 2015) - Bontempo, R.; Cardone, M.; Manna, M.; Vorraro, G.
Highlights: Steady and unsteady characteristics of a turbocharger are analysed by experimental means. The steady state characteristic maps are obtained for both the compressor and the turbine. The validity of the classical adiabatic assumption is questioned. The compressor efficiency evaluated through the adiabatic assumption may lead to a 5–10% relative error. The mild and deep compressor surge phenomena have been experimentally investigated. Abstract: The paper describes the steady and unsteady performance characteristics of a small size turbocharger typically employed in automotive downsized engine applications. The analysis is carried out by experimental means using an innovative hot gas generator system specifically designed for turbocharger testing which is capable of delivering a wide range of flow rates with adequate thermodynamic characteristics. More in detail, the gas generator consists of a medium size direct injection compression ignition Internal Combustion Engine (ICE) feeding the turbine of the test article. To independently set the hot gas mass flow rate and the turbine inlet temperature, the operating parameters of the aforementioned ICE are specified through an electronic control unit in a fully automated manner. Compared to previously presented data [1] (Energy Procedia, vol. 45, pp 1116-1125, 2014), those reported herein have been collected with the help of newly installed equipment and controlling software allowing for the estimation of the thermal power transferred from the turbocharger to the environment. In particular, thanks to a first law analysis, the collected measurements have shown that the algebraic sum of the thermal power transferred to the lubricating oil as well as to the environment is roughly speaking 20–30% of the compressor total enthalpy change per unit time. Moreover, it has been shown that evaluating the compressor efficiency through classical expression based on the adiabatic assumption leads to a 5–10% relative error. The improved experimental set up also allows for higher precision transient analysis both on the cold and hot side branch of the test article. While the steady-state performance maps of the turbocharger are readily obtained with the semi-automated testing procedure, the detailed analysis of the unsteady phenomena related for instance to the occurrence of mild and deep compressor surge events, are reproduced and thoroughly analysed using the rig in more advanced operating modes.